Vibration Effect on the SMS Fiber Structure - Ika Puspita; A. M. Hatta; Sekartedjo Sekartedjo; Ayu Kusumawardhani (IPTEK Journal of Proceedings Series, 2015)
We present a preliminary result on the singlemode-multimode-singlemode (SMS) fiber structure for a vibration sensor. The SMS fiber structure was placed in a macrobender within the mechanical transducer to detect the frequency of a vibration source. The time series of optical output power of the SMS fiber structure was measured and it was transformed into the frequency domain using the fast Fourier transform. It was demonstrated that the frequency of vibration source can be determined by using the mechanical transducer with the SMS fiber structure. It was also analyzed the distance effect between the source and the SMS fiber structure. It was shown that the frequency measurement of 20 Hz vibration source can be carried out in a range of 0 to 30 cm with an error frequency 0.1 Hz. This scheme is potential for the vibration measurement which offers inexpensive and simple configuration.